Current Status of the Disease-Resistant Gene(s)/QTLs, and Strategies for Improvement in Brassica juncea - Singh, Kaushal Pratap; Kumari, Preetesh; Rai, Pramod Kumar (Frontiers in Plant Science, 2021)
Brassica juncea is a major oilseed crop in tropical and subtropical countries, especially in south-east Asia like India, China, Australia, Bangladesh, and Pakistan. The widespread cultivation of genetically similar varieties tends to attract fungal pathogens which cause heavy yield losses in the absence of resistant sources. The conventional disease management techniques are often expensive, have limited efficacy, and cause additional harm to the environment. A substantial approach is to identify and use of resistance sources within the Brassica hosts and other non-hosts to ensure sustainable oilseed crop production. In the present review, we discuss six major fungal pathogens of B. juncea: Sclerotinia stem rot (Sclerotinia sclerotiorum), Alternaria blight (Alternaria brassicae), White rust (Albugo candida), Downy mildew (Hyaloperonospora parasitica), Powdery mildew (Erysiphe cruciferarum), and Blackleg (Leptoshaeria maculans). From discussing studies on pathogen prevalence in B. juncea, the review then focusses on highlighting the resistance sources and quantitative trait loci/gene identified so far from Brassicaceae and non-filial sources against these fungal pathogens. The problems in the identification of resistance sources for B. juncea concerning genome complexity in host subpopulation and pathotypes were addressed. Emphasis has been laid on more elaborate and coordinated research to identify and deploy R genes, robust techniques, and research materials. Examples of fully characterized genes conferring resistance have been discussed that can be transformed into B. juncea using advanced genomics tools. Lastly, effective strategies for B. juncea improvement through introgression of novel R genes, development of pre-breeding resistant lines, characterization of pathotypes, and defense-related secondary metabolites have been provided suggesting the plan for the development of resistant B. juncea.